1997
DOI: 10.1007/s11357-997-0010-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary restriction and exercise on the age-related pathology of the rat

Abstract: Intervention of the aging process is an effective, experimental means of uncovering the bases of aging. The most efficacious and commonly used intervention used to retard the aging processes is dietary restriction (DR). It increases mean and maximum life spans, delays the appearance, frequency, and severity of many age-related diseases, and more importantly, attenuates much of the physiological decline associated with age. Although the subject of intense research, the mechanism by which DR alters the aging pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…What are the effects of lipid restriction on longevity? Many studies have discussed whether or not lipids are involved in CR effects, some supporting and some rejecting this idea based on different kinds of endpoint biochemical measurements and experiments 36–39 . But very few studies have directly tested the effect of lipid restriction on longevity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What are the effects of lipid restriction on longevity? Many studies have discussed whether or not lipids are involved in CR effects, some supporting and some rejecting this idea based on different kinds of endpoint biochemical measurements and experiments 36–39 . But very few studies have directly tested the effect of lipid restriction on longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have discussed whether or not lipids are involved in CR effects, some supporting and some rejecting this idea based on different kinds of endpoint biochemical measurements and experiments. [36][37][38][39] But very few studies have directly tested the effect of lipid restriction on longevity. In a long-term study in Fisher 344 rats, increases in maximum and medium life span were found after 40% CR but not after 40% lipid restriction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, most physiological, biochemical and pathological changes with age are delayed or reduced in CR rodents compared to ad libitum fed controls (reviewed in [6]). Age-related development of insulin resistance [142], declines in immune function [143,144], and alterations in neural and behavioral parameters [145,146] are all reduced by CR, and the onset and incidence of age-associated diseases including neoplasia and nephropathies are delayed [147–149], among many other examples. Additionally, the long-lived Ames/Snell dwarf mutations show reduced occurrence or severity of age-related pathologies such as collagen aging [150], osteoarthritis [151], the development of cataracts [152], glomerular nephrosis [152], age-related cognitive decline [153,154], and the slowed progression of multiple forms of spontaneous neoplasia [152,155].…”
Section: Do Alterations In the Expression Of Antioxidant Genes In Labmentioning
confidence: 99%
“…Caloric restriction was shown to reduce the rate of mitochondrial reactive oxygen species production and the rate of oxidative attack to biological macromolecules such as mitochondrial deoxyribonucleic acid (DNA) in rodents (Kim et al, 1996;Ikeno et al, 1997;Masoro, 1998;Lindsay, 1999;Lal et al, 2001;López-Torres et al, 2002). The use of total diet replacements for weight control in obese subjects resulted in a decline in oxidative stress markers, especially in patients with metabolic syndrome (Tzotzas et al, 2008;Tumova et al, 2013).…”
Section: Vitamin Cmentioning
confidence: 99%